Mastering import & export management - Cook, Thomas A., 1953-; Alston, Rennie; Raia, Kelly (American Management Association, 2012)
With billions of dollars generated annually, importing and exporting is a potentially lucrative arena for growthùand a bewildering tangle of rules and regulations. Packed with hundreds of cost-effective strategies, ready-to-use forms, and valuable checklists, the second edition of Mastering Import & Export Management explains how to efficientlyùand legallyùnavigate the complex world of international trade. From the big picture of pinpointing the best markets to the nitty-gritty of packing a container, this sweeping guide examines how to spot potential risks, apply quality control procedures, p.